Determinants of Islamic Bank Share Price Fluctuation During the Covid 19 Pandemic: The Case of BTPN Syariah Bank Shares - Farhan Lauda; Resfa Fitri; Qoriatul Hasanah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. The Covid-19 pandemic has caused a decline in the performance of the national economy. However, the share price of Islamic banks, especially the BTPN Syariah Bank (BTPS), has continued to grow. This study aims to identify and evaluate the variables affecting BTPS stock price fluctuation, using The Vector Error Correction Model (VECM). The results show that in the short term, only the Jakarta Composite Index variable had a significant effect on the stock price of BTPS. While in the long term, the variables of Price to Book Value (PBV), Trading Volume Activity (TVA), GDP, Bank Indonesia (BI) Reference Interest Rate, and the Jakarta Composite Index had a significant effect on BTPS stock price. Based on the Impulse Response Function (IRF) analysis, the stock price of BTPS responded negatively to shocks in GDP, TVA, and the exchange rate. Meanwhile, the shocks of Earning Per Share, PBV, BI Reference Interest Rate, and the Jakarta Composite Index were responded positively by BTPS share price. Based on the Forecast Error Variance Decomposition analysis, PBV gave the highest contribution in explaining the diversity of BTPS stock prices fluctuation.Keywords: Covid-19, BTPS Shares, VECM, Internal Factors, External FactorsAbstrak. Pandemi Covid-19 menyebabkan penurunan perekonomian nasional. Namun, harga saham bank syariah, khususnya saham PT. Bank BTPN Syariah (BTPS) tetap tumbuh. Penelitian ini bertujuan untuk mengetahui faktor yang memengaruhi perubahan harga saham BTPS, dengan metode Vector Error Correction Model (VECM). Hasil penelitian menunjukan bahwa dalam jangka pendek, hanya variabel Indeks Harga Saham Gabungan yang berpengaruh signifikan terhadap harga saham BTPS. Sementara pada jangka panjang, variabel Price to Book Value (PBV), Trading Volume Activity (TVA), PDB, Suku Bunga Acuan Bank Indonesia (BI), dan Indeks Harga Saham Gabungan berpengaruh secara signifikan terhadap harga saham BTPS.  Berdasarkan analisis Impulse Response Function (IRF), harga saham BTPS merespon negatif adanya guncangan PDB, TVA, dan nilai tukar. Sementara guncangan Earning Per Share, PBV, Suku Bunga Acuan BI, dan Indeks Harga Saham Gabungan direspon positif oleh harga Saham BTPS. Berdasarkan analisis Forecast Error Variance Decomposition, PBV memberikan kontribusi tertinggi dalam menjelaskan keragaman perubahan harga saham BTPS.Kata kunci: Covid-19, Saham BTPS, VECM, Faktor Internal, Faktor Eksternal